THE CURRENT SITUATION OF CADMIUM AND MERCURY IN MILK AND DAIRY PRODUCTS IN CAN THO IN 2021 (Vietnam Journal of Community Medicine, 2022)
Introduction: Milk and dairy products are foods with nutritional value. Milk will be unsafe if theconcentration of heavy metals in milk exceeds the allowable standard.Objective: Determination of Cd, Hg concentration in milk and dairy products in CanTho City, 2021.Objects and methods: 250 samples of liquid milk, yoghurt, cheese, milk cake and powdered milkwere sampled and analyzed quantitatively for heavy metals. Samples were inorganic before analysisto remove organic compounds, and determined by atomic absorption spectroscopy.Results: The average concentration of Cd, Hg in liquid milk was 102.03 ppb; 33.28 ppb; in yogurt44.82 ppb; 33.48 ppb; in cheese 67.64 ppb; 26.05 ppb; in milk cakes 50.49 ppb; 16.83 ppb; in milkpowder 5.89 ppb; 6.28 ppb.Conclusion: While the concentration of Hg in our study in some samples was higher than theallowable standard (14,00%), the quantification of Cd was below the permissible standard and maynot affect the health of consumers of milk and dairy products.
Keywords: Cadmium, Mercury, Milk, Dairy products.